Experimental Study on the Effect of Expansive Agent on the Durability of Concrete in Civil Air Defense Engineering - Junbo Zhang; Jigang Zhang; Weiwei Xiao; Qianying Wang; Feng Shao (Advances in Materials Science and Engineering)
In this study, the effect of 8% UEA the reason why the UEA content is 8% is as follows: the expansion agent content in the actual mix proportion of the project is 8%, which is selected in this test to fit the reality better. expansion agent on the compressive strength, chloride ion penetration resistance, and carbonation resistance of civil air defense concrete were studied by simulating the rapid carbonation and chloride solution immersion of concrete structure in coastal civil air defense engineering environment. The results of this study show that the early compressive strength of concrete decreased by adding the UEA expansion agent and was also affected by the curing time. Moreover, the addition of UEA expansion agent decreased the content of free chloride ions and calcium carbonate in concrete and reduced the early compressive strength of concrete.